2011
DOI: 10.1111/j.1447-0594.2011.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for the Timed Up and Go test in healthy Japanese elderly people: Determination using the methodology of meta‐analysis

Abstract: The reference values of TUG in Japanese healthy elderly people calculated in this study are certainly shorter than in African-Americans and Caucasians. The reference values of TUG estimated by our study appear to be specific for healthy, elderly, Japanese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 31 publications
1
43
1
1
Order By: Relevance
“…The search terms used were ''hand grip strength/akuryoku,'' ''hand strength,'' ''grip,'' ''grasp,'' ''strength,'' ''power,'' ''older people/koureisya,'' ''aged,'' and ''elderly'' in appropriate combinations. The selection criteria for papers used in the meta-analysis were set as follows in accordance with earlier studies [12][13][14][15]: (1) papers written in Japanese or English; (2) papers on Japanese community-dwelling people aged C60 years old; (3) papers on community-dwelling elderly independent in activities of daily living (ADLs); (4) papers not examining frail elderly or elderly with an evident disease; (5) papers reporting measurements in kilograms or Newtons; (6) papers reporting data on hand grip strength by sex; and (7) papers listing the number of subjects and the mean and standard deviation (SD) of hand grip strength. Four researchers (NK, RK, TN, and MA) held discussions to determine search terms to use and which papers to include in the analysis.…”
Section: Paper Retrieval Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search terms used were ''hand grip strength/akuryoku,'' ''hand strength,'' ''grip,'' ''grasp,'' ''strength,'' ''power,'' ''older people/koureisya,'' ''aged,'' and ''elderly'' in appropriate combinations. The selection criteria for papers used in the meta-analysis were set as follows in accordance with earlier studies [12][13][14][15]: (1) papers written in Japanese or English; (2) papers on Japanese community-dwelling people aged C60 years old; (3) papers on community-dwelling elderly independent in activities of daily living (ADLs); (4) papers not examining frail elderly or elderly with an evident disease; (5) papers reporting measurements in kilograms or Newtons; (6) papers reporting data on hand grip strength by sex; and (7) papers listing the number of subjects and the mean and standard deviation (SD) of hand grip strength. Four researchers (NK, RK, TN, and MA) held discussions to determine search terms to use and which papers to include in the analysis.…”
Section: Paper Retrieval Methodsmentioning
confidence: 99%
“…However, other reports have suggested that racial differences exist in hand grip strength and other physical performance tests [11,12]. Therefore, reference values not based on measurements in Asians [9] are not appropriate for Japanese people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was some early concern about the TGUG test-retest reliability 36 further studies demonstrated that TGUG is a good measure of physical capability in older adults. 12,13,[37][38][39] Nevertheless, the lack of association between sarcopenia and the TGUG test has been found by others. 40,41 Merriwether et al 41 have studied 154 community-dwelling older adults (72% women) and found no relationship between sarcopenia defined as Baumgartner suggested and physical performance.…”
Section: Discussionmentioning
confidence: 95%
“…All women were asked to sit in a 43-cm chair. 12,13 The time to get up, walk a 3-meter distance, walk back and sit again was recorded. Muscle strength was measured with a handgrip dynamometer (Jamar Hydraulic Hand Dynamometer, Sammons Preston, Chicago, IL), according to the American Society for Hand Therapists Society recommendation.…”
Section: Assessmentsmentioning
confidence: 99%